Counselove: Marital Counseling Android-based Application to Promote Marital Satisfaction - Widodo Budiharto; Meliana Meliana; Pingkan C.B. Rumondor (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper presents the development of Android-based framework for improving marital satisfaction. Classic research in psychology found that stability of marriage is based on the ability to create and maintain a positive interaction ratio five times more than negative interactions. Based on that, we present Counselove, a mobile application intended to record information of daily positive behaviors (joking, showing affection) of couples who use the application. We propose a method where the apps can determine users’ marital satisfaction level and also can help users increasing their marital satisfaction based on the relationship satisfaction questionnaire and the assessment of user’s self reported behaviors to their partners using fuzzy logic. The experimental results shown the application is running well on mobile devices based on Android platform. Lastly, we provide result of in depth interview with two users. Further research and development of the Counselove apps are discussed.